Trigona PENGARUH POSISI PINTU MASUK TERHADAP PERKEMBANGAN SARANG KOLONI LEBAH Trigona sp. - Daud Irundu; Muhammad Fahmin; Rita Bulan; Zulkahfi z (Program Studi Kehutanan Universitas Muslim Maros, 2022)
ABSTRACT The development of the Trigona sp. beehive affects the productivity of the bee, especially in hive building. The position of beehive’s trigona entrance has an influence on trigona bee ability to build a hive. Increasing the access of bees in building hive will increasing the component of of the beehive. This study was used bee boxes with various of beehive entrance position as observed factors namely top vertical, bottom vertical, and horizontal. The study was carried out from November 2021 to March 2022. The method used 9 units of stup samples with 3 replications for each treatment. The parameters were the weight and dimensions measurement of the hive based on a scale approach on the stup wall. Analysis used one-way Anova (Analysis variance) and BNJ test. The result showed that the largest average of hive weight was 2.679,5 grams in the bottom vertical entrance position treatment. On the other hand, there was significant affect (P<1%) of the entrance position to development of stup dimensions. BNJ test (P<1%) of stup dimensions showed that bottom vertical entrance treatment had different affect to top vertical and horizontal entrance treatment, where bottom vertical entrance treatment had the largest increase of stup dimensions.